Heterotopic bone formation following anterior cruciate ligament reconstruction with BPTB autograft - Erdil, Mehmet; Asik, Mehmet; Sen, Cengiz; POLAT, Gökhan (My University, 2012)
In this study, we present a 36-year-old male patient who developed heterotopic ossification after anterior cruciate ligament (ACL) reconstruction performed using bone-patellar tendon-bone autograft harvested from the 1/3 middle part of the patellar tendon. This ossified part, which restricted range of motion of the affected knee, was excised surgically 1 year after diagnosis. Physical examination, conducted 36 months later, revealed the achievement of full range of motion without any complaints or recurrences. Heterotopic ossification following ACL reconstruction is a very rare complication, which should be removed with open surgery.
Keywords: BPTB